Intercollegiate perfectionistic athletes' perspectives on success and failure in sport. Issue 1 (2nd January 2022) - Gotwals, John K.; Tamminen, Katherine A.
Abstract: This study explored perfectionistic athletes' perspectives on and experiences of success and failure in sport through a three-phase mixed methods design. In Phase 1, 122 intercollegiate varsity athletes responded to the Sport Multidimensional Perfectionism Scale 2. Ten athletes were then purposively sampled who, based on the percentile rank of their subscales scores, endorsed pure personal standards perfectionism ( n = 3) or mixed perfectionism ( n = 7). In Phases 2 and 3, these ten athletes took part in semi-structured interviews that explored meaningful experiences of success and failure from their past and a diary protocol that chronicled their actual experiences of success and failure over a season. Thematic analysis of the data indicated that the perfectionists' perspectives on success and failure revolved around the pursuit of forward momentum in sport. This theme was enabled by the sport context and was reflected in active resistance to contentment, a prioritization of perpetual improvement, and a continual re-direction of attention to future challenges. Subthemes indicated how forward momentum was fueled and challenged by concerns over athletic legitimacy and fostered through hard work. The pure personal standard perfectionists and the mixed perfectionists showed similarities and differences within each subtheme as well as in their reactions to stalled momentum. The specific patterns of findings suggested that the mixed perfectionists were relatively more likely to respond to failure in a manner reflective of narrative wreckage and perfectionistic reactivity. The practical implications of these findings are discussed. Lay summary: Through interviews and season-long diaries, this study explored ten perfectionistic athletes' perspectives on success and failure. Findings revolved around desires to continually improve, demonstrate legitimacy, and work hard. The degree to which these perspectives were associated with negative responses to failure generally depended on the specific form of perfectionism endorsed. Practical implications: It is important to recognize the nature of athletes' perfectionistic tendencies as pure personal standard perfectionists and mixed perfectionists reported meaningful similarities and differences in how they conceptualize, experience, and respond to success and failure in sport. Mixed perfectionistic athletes appeared to endorse a set of irrational beliefs that contributed to their vulnerability to distress following failure. Cognitive-behavioral therapy could be used to address these irrational beliefs. Following the success, coaches and practitioners should be attentive to developments in perfectionistic athletes' beliefs and foster their ability to adaptively appraise and cope with emergent demands. Practitioners adopting a narrative approach to therapy and working with intercollegiate athletes who endorse pure personal standards perfectionism or mixed perfectionism could use the present findings to help the athletes make meaning about their own experiences of success and failure.